Analysis of Public Expenditure Policy Regime and Its Relationship with Economic Growth over Different Political Regimes of Nepal - Bista, Raghu Bir; Khatri, Bishnu Bahadur (NUTA Journal, 2022)
This study analyzes trend and pattern of public expenditure and relationship with economic growth in Nepal by using descriptive, trend, ratio and correlation method based on secondary data from 1975 to 2019. As a result, a trend of recurrent expenditure (RE) is inclining with positive growth, a trend of government expenditure (GE) is also inclining. However, it is different in case of capital expenditure (CE) because of consistent trend. Recurrent expenditure is unnecessarily expansionary but capital expenditure is unnecessarily contractionary. Recurrent expenditure (RE) is positively correlated with Government expenditure (GE) and capital expenditure (CE) is negatively correlated with Government expenditure (GE). It shows the expansionary budgetary policy doesn’t influence on CE but can be seen in GE and RE. Lastly, the annual positive change of regular expenditure in the share of public expenditure is higher than in the share of GDP. Whereas, the annual negative change of capital expenditure in the share of public expenditure is higher than in the share of GDP. Thus, uncontrolled expansionary regular expenditure and unnecessarily contractionary capital expenditure are big issues to macro-economic stability and higher economic growth of Nepal. This paper is expected to contribute to understand public expenditure and its linkage with economic growth and to formulate public expenditure framework.